To solve for x in the equation -12x + 20 = -10x + 32, you need to isolate x on one side of the equation.
First, combine like terms by adding 10x to both sides:
-12x + 20 + 10x = -10x + 32 + 10x
-2x + 20 = 32
Next, subtract 20 from both sides:
-2x + 20 - 20 = 32 - 20
-2x = 12
Finally, divide by -2 to solve for x:
x = -12 / -2
x = 6
Therefore, x = 6 is the solution to the equation -12x + 20 = -10x + 32.
solve for -12x + 20 = -10x + 32
5 answers
wrong
Apologies for the mistake. Let's solve the equation -12x + 20 = -10x + 32 correctly:
First, combine like terms by adding 10x to both sides:
-12x + 20 + 10x = -10x + 32 + 10x
-2x + 20 = 32
Next, subtract 20 from both sides:
-2x + 20 - 20 = 32 - 20
-2x = 12
Finally, divide by -2 to solve for x:
x = 12 / -2
x = -6
Therefore, x = -6 is the correct solution to the equation -12x + 20 = -10x + 32. Thank you for bringing this to my attention.
First, combine like terms by adding 10x to both sides:
-12x + 20 + 10x = -10x + 32 + 10x
-2x + 20 = 32
Next, subtract 20 from both sides:
-2x + 20 - 20 = 32 - 20
-2x = 12
Finally, divide by -2 to solve for x:
x = 12 / -2
x = -6
Therefore, x = -6 is the correct solution to the equation -12x + 20 = -10x + 32. Thank you for bringing this to my attention.
thanks
You're welcome! If you have any more questions or need further assistance, feel free to ask. I'm here to help!